Os dilemas do caráter público da política de assistência social: uma reflexão a partir da visão das(os) trabalhadoras(es) do Sistema Único de Assistência Social (SUAS) da região central da cidade de São Paulo - Souza, Nájila Thomaz de (2016)
This dissertation discusses the political and ideological implications of the partnership between the State and organizations without Fins Economic (OSFE), from the perspective of (the) working (s) of the Unified Social Assistance System (SUAS) working in Sé Social Supervision, (SAS Sé) of the Secretary Municipal Social Assistance and Development (SMADS) of the Municipal City Hall of São Paulo (PMSP). We understand that the transfer of state functions to civil society are part of state reform process, in the face of the productive of capitalism restructuring. In this particular case, the SUAS of (the) working (s) living with flexibility, precariousness and loss expressed labor rights in the world of contemporary work. The dissertation analyzes a critical way on from the historical and dialectical materialism the apprehension of reality in its entirety the categories that articulate themselves in the professional routine. The methodology includes bibliographical and documental and qualitative research professionals, by carrying out two focus groups: one with the working of OSFE working in the central area of São Paulo, and another with public servants of Sé Social Services Supervision. We try to understand their perceptions about the public character of social assistance policy, highlighting the presence of OSFE that have religious missions and the secularity of the SUAS. Also we problematize the conditions of precariousness, flexibility and outsourcing the work process in the SUAS and the relationship, sometimes conflicting and hierarchic between workers and can be seen in technical supervision of social assistance services. The bibliographic content and focus groups allows us to to infer that this partnership has contributed to the loss of the public character of the SUAS, reinforced the precariousness of the work process and establishing unequal relations between workers, for that very reason arises as one of great challenges to be faced by the Social Assistance Politics